Evidence of Insulin Resistance in Adult Uncomplicated Malaria: Result of a Two-Year Prospective Study. (22nd December 2014) - Acquah, Samuel; Boampong, Johnson Nyarko; Eghan Jnr, Benjamin Ackon; Eriksson, Magdalena
Abstract : The study aimed at investigating the effects of adult uncomplicated malaria on insulin resistance. Fasting levels of blood glucose (FBG), glycosylated hemoglobin (HbA1c), and serum insulin were measured in 100 diabetics and 100 age-matched controls before and during Plasmodium falciparum malaria. Insulin resistance and beta cell function were computed by homeostatic models assessment of insulin resistance (HOMAIR) and beta cell function (HOMAB) formulae, respectively. Body mass index (BMI) was computed. At baseline, diabetics had significantly ( P < 0.05 ) higher levels of BMI, FBG, HbA1c, and HOMAIR but lower level of HOMAB than controls. Baseline insulin levels were comparable ( P > 0.05 ) between the two study groups. During malaria, diabetics maintained significantly ( P < 0.05 ) higher levels of BMI, FBG, and HbA1c but lower levels of insulin and HOMAB than controls. Malaria-induced HOMAIR levels were comparable ( P > 0.05 ) between the two study groups but higher than baseline levels. Apart from BMI and HOMAB, mean levels of all the remaining parameters increased in malaria-infected controls. In malaria-infected diabetics, significant ( P < 0.05 ) increase was only observed for insulin and HOMAIR but not the other measured parameters. Uncomplicated malaria increased insulin resistance in diabetics and controls independent of BMI. This finding may have implications for the evolution of T2DM in malaria-endemic regions.